Factors Influencing the Safety and Health Performance of Construction Site Workers in Johor Bahru, Johor - MOHD SAYID NASIR, MUHAMMAD AFIQ; SYED MOHAMAD, SYED BURHANUDDIN HILMI (Recent Trends in Civil Engineering and Built Environment, 2022)
In this era of globalization, the construction industry has been recognized as one of the most hazardous industries and workers in this industry are more at risk of accidents that can injure, disfigure, or even death. The main purpose of this study is to determine the factors that influence the safety and health performance of construction site workers and assess the level of compliance with existing safety and health work systems or procedures at the construction site targeted for the construction firms in Johor Bahru that are registered as Grade 1-7 and construction industry professionals. The research method adopted in the present study was the quantitative method involving the deliver and collect questionnaire using Likert scale and through the data analyzed by using Average Index (AI) for gaining precise results. This research will benefit construction site workers and contractors involved in the industry of construction by providing good information for them to highlight and providing workers and individuals participating in the building process with safety practices and comply safety rules and laws while on the construction site. This research revealed that having safety meetings implement can improve the safety and health of construction site workers and the execution of emergency planning and preparation was essential due to the most compliance factors. Finally, to improve the safety and health of construction site workers, a set of recommendations were made and topics for future researches were suggested